Managing Stress During the Holidays - Heidi Radunovich (EDIS)
When we think of the holidays, we often think about family, togetherness, giving, and celebrating. While the holiday season should be a time of enjoyment, there are many events associated with the season that can cause stress. This 3-page fact sheet was written by Heidi Radunovich, and published by the UF Department of Family Youth and Community Sciences, November 2013. http://edis.ifas.ufl.edu/fy1404